2012
DOI: 10.3892/or.2012.1761
|View full text |Cite
|
Sign up to set email alerts
|

Associated microsatellite alterations in mitochondrial DNA and in TP53 in thoracic esophageal squamous cell carcinoma

Abstract: Abstract. We investigated the microsatellite alterations in mitochondrial DNA (mtDNA) and in TP53 in thoracic esophageal squamous cell carcinomas (TESCC). Using laser microdissection, 66 paired non-cancerous esophageal muscles, non-cancerous esophageal mucosa, cancerous TESCC nests plus 35 metastatic lymph nodes harvested from 66 resected esophagi of TESCC patients were subjected to DNA extraction. D310 and D17S960 were chosen as markers to address microsatellite alterations in mtDNA, including changes in copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…During the past 20 years, alterations of mtDNA copy number in several human cancers had been extensively investigated [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 34 , 35 ]. Simonnet et al and Meierhofer et al demonstrated a decrease of mtDNA copy number and a decline of mitochondrial enzyme activity in human RCC and such a decrease was associated with the aggressiveness of RCC [ 29 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past 20 years, alterations of mtDNA copy number in several human cancers had been extensively investigated [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 34 , 35 ]. Simonnet et al and Meierhofer et al demonstrated a decrease of mtDNA copy number and a decline of mitochondrial enzyme activity in human RCC and such a decrease was associated with the aggressiveness of RCC [ 29 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of mtDNA copy numbers in human cancers have been extensively studied [ 15 , 16 , 17 ]. An increase of the mtDNA copy number was noted in head and neck cancers, or esophageal squamous cell carcinoma, especially cigarette smokers [ 18 , 19 , 20 , 21 , 22 ]. Such an increase was supposed to compensate for the damaged mtDNA to keep the supply of ATP by mitochondrial respiration above a threshold.…”
Section: Introductionmentioning
confidence: 99%